"Not lazier, I'm Sharper with AI": Analyzing How Artificial Intelligence Restructures Students’ Cognition - Sitti Jamilah; Nyak Mutia Ismail; Sepri Kurniadi (Jurnal Sociohumaniora Kodepena (JSK), 2025)
This qualitative case study explores how AI assistance influences students’ cognition in English academic writing. With 18 undergraduate students in an Academic Writing course as research participants, the study compares assignments and reflections that were created with and without the aid of AI. Data were collected through two main sources: a set of written assignments (one non-AI-assisted and one AI-assisted per student) and reflective personal statements detailing students’ learning experiences. The primary instruments included a qualitative analytic framework adapted from a writing rubric to guide close reading and thematic coding of both assignments and reflections. Data analysis was conducted through comparative content analysis and thematic analysis, focusing on key dimensions such as argumentation, organization, creativity, grammar, and real-world awareness. The findings suggest that AI-assisted writing not only supports surface-level features, such as grammar and vocabulary, but also fosters deeper argument, organization, and critical engagement skills. Many students expressed greater confidence and an enhanced awareness of problems in the world, saying that AI had led the way to more effective, independent thinking; but the analysis emphasizes that the extent of cognitive reframing varies significantly depending on how purposefully and critically students interact with AI tools. Conclusively, the results contribute to the ongoing discussion of AI in higher education: when used thoughtfully, AI can be a complementary pedagogical partner that enhances higher order thinking and self-efficacy. The study recommends further research in different contexts and on long-term outcomes.